2022
DOI: 10.1177/09596836221131708
|View full text |Cite
|
Sign up to set email alerts
|

Modeled dispersal patterns for wood and grass charcoal are different: Implications for paleofire reconstruction

Abstract: Sedimentary charcoal records provide useful perspectives on the long-term controls and behavior of fire in the Earth System. However, a comprehensive understanding of the nuances, biases, and limitations of charcoal as a fire proxy is necessary for reliable paleofire interpretations. Here, we use a charcoal dispersal model to answer the following questions: (1) How does the dispersal of wood and grass charcoal particles differ? (2) Do traditional conceptual models of charcoal dispersal reliably characterize gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…An increase in pollen influx is usually associated with an increase in fire intensity and a shorter distance from its source (Tinner et al, 2006;Duffin et al, 2008). Experimental analysis of charcoal particles has shown that the charcoal area increases with local fire (Leys et al, 2015(Leys et al, , 2017, especially when charred wood particles are more abundant (Vachula and Rehn, 2023). From 810 to 730 cal a BP, a mid-magnitude fire event (CHARarea <4 mm 2 cm −2 a −1 ) with gradual increase in charred grass particles (Figs 4 and S4) was observed after a short dry episode, and did not prevent the expansion of woody cerrado and gallery forest taxa, with a recovery of about 12 years.…”
Section: Fire Events In Central Brazilmentioning
confidence: 99%
“…An increase in pollen influx is usually associated with an increase in fire intensity and a shorter distance from its source (Tinner et al, 2006;Duffin et al, 2008). Experimental analysis of charcoal particles has shown that the charcoal area increases with local fire (Leys et al, 2015(Leys et al, , 2017, especially when charred wood particles are more abundant (Vachula and Rehn, 2023). From 810 to 730 cal a BP, a mid-magnitude fire event (CHARarea <4 mm 2 cm −2 a −1 ) with gradual increase in charred grass particles (Figs 4 and S4) was observed after a short dry episode, and did not prevent the expansion of woody cerrado and gallery forest taxa, with a recovery of about 12 years.…”
Section: Fire Events In Central Brazilmentioning
confidence: 99%
“…Charcoal morphometrics based on aspect ratio can successfully differentiate woody and grass fuels (Vachula et al, 2021), however, previous studies document the overrepresentation of woody charcoal in grass dominated systems (Leys et al, 2015). To complicate this issue, recent charcoal dispersal models indicate that the dispersal of wood versus grass charcoal is not uniform, with fine grass charcoal particles being transported further than woody charcoal particles of the same size class (i.e., 125 µm) (Vachula and Rehn, 2023). Thus, the grass-charcoal component present in charcoal records from grass-dominated and mixed wood-grass ecosystems, such as NKMNP, likely represent broader regional fire histories than woody charcoal records from wood-dominated ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, dispersal models accounting for shapes, sizes and densities of charcoal show that small differences in shape and density of charcoal can cause substantial differences in particle source area (Vachula and Richter, 2018;Vachula and Rehn, 2023). Elongated, lighter particles such as those from graminoids tend to have higher residence time in the atmosphere and can travel longer distances than spherical or heavier particles, such as those from leaves or wood (Clark and Hussey, 1996;Pisaric, 2002;Vachula and Richter, 2018;Courtney Mustaphi et al, 2022;Vachula and Rehn, 2023). Charcoal particles produced by grassland fires tend to be smaller than those produced by forest fires (Belcher et al, 2005;Leys et al, 2017), and our results show that the size of charcoal particles decreased with the increased fire temperature.…”
Section: Application Of Charcoal Morphologies Andmentioning
confidence: 99%
“…Another uncertainty in charcoal-based fire reconstruction is how charcoal production is affected by the biomass quantity, density, moisture content and fire temperature (Simpson et al, 2016;Pereboom et al, 2020;Feurdean, 2021;Hudspith et al, 2018). Finally, the size, shape and density of the charcoal fragments can cause substantial differences in particle dispersal and incorporation into sediments (Clark and Hussey, 1996;Vachula and Richter, 2018;Vachula and Rehn, 2023). Microscopic particles may be transported considerable distances and deposited into various sedimentary environments such as peats, lakes and rivers, in contrast to larger particles that tend to be deposited nearer to the source of the fire (Scott et al, 2000;Scott, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation